HUBUNGAN ANTARA KECERDASAN EMOSIONAL DENGAN MORALE KERJA PADA KARYAWAN BALAI BESAR LATIHAN KERJA INDUSTRI (BBLKI) SURAKARTA - Wahyuningsih, Triani (TALENTA, 2014)
Important source in any company or organization is human. This study aims  to  determine  1)  the  relationship  between  emotional  intelligence  with  work  on employee  morale,  2)  the  role  of  emotional  intelligence  to  work  morale,  3)  the  level  of emotional  intelligence  on  the  subject  of  research,  4)  the  level  of  morale  working  on research  subjects.  The  hypothesis  is  a  positive  relationship  between  emotional intelligence  with  work  on  employee  morale.  Subjects  in  this  study  were  employees  of Center  for  Industrial  Training  (BBLKI)  Surakarta.  The  population  of  120  people.  The samples  in  this  study  using  purposive  sampling,  with  the  characteristics  of  the  study subjects: 1) subjects aged between 30-60 years, 2) Working period between 20 s / d 40 years.  Subject  retrieval  technique  used  is  nonrandom  sampling.  Based  on  calculations using  analytical  techniques  derived  product  moment  coefficient  (r)  of  0.296  with  p  = 0.020 (p <0.05). This means the hypothesis is accepted that there is a significant positive relationship  between  emotional  intelligence  with  work  on  employee  morale.  That  is emotional  intelligence  veriable  depat  used  as  a  predictor  for  predicting  work  on employee morale.